Alveolar Bone Grafting Changes the Inclination of Teeth and Affects Malocclusion in Patients With Unilateral Alveolar Cleft. Issue 5 (July 2017) - Kim, Jeenam; Shin, Hyojeong; Uhm, Ki-il; Shin, Donghyeok; Choi, Hyungon
Abstract : Introduction: Alveolar bone grafting not only stabilizes the alveolar arch, but also provides positive aesthetic outcomes. However, there have been no reports about the inclinations of the incisor and canine or the change in occlusion after alveolar bone grafting. Therefore, the purpose of this study is to analyze the effects of alveolar bone grafting on tooth angles and changes in occlusion in patients with a unilateral alveolar cleft, using three-dimensional computed tomography. Methods: The authors retrospectively studied alveolar bone grafts performed in Konkuk University Medical Center between January 2008 and January 2013. A total of 40 patients with unilateral alveolar cleft were included in this study; the authors measured the changes in tooth angles and changes in anterior and molar occlusion before and after bone grafting. Results: Of the 40 patients enrolled, 21 completed follow-up and had adequate computed tomography imaging studies. Ten patients who were lost during the follow-up period, and 9 with inadequate images, were excluded. The anterior occlusion increased from −2.21 to 0.19 mm ( P < 0.0001) and the molar occlusion increased from 0.75 to 2.10 ( P < 0.0001). The dental angle decreased from 25.23° to 15.32° ( P = 0.001). Discussion: Alveolar bone grafting provides support to the tooth root and changes the inclination of the tooth, resulting in changes in occlusion and positive aesthetic outcomes.